Решите пожалуйста ( с объяснением, если можно): ( Ответ: )

  • 24-01-2007 05:22
  • Просмотры: 99
Ответы ( 1 )
Лена Москаленко
+1
24-01-2007 07:40

Sin(2/3 -x/4)*cos(/6+x/4)*sinx/4 = 1/2 *(sin(2/3 - x/4 +/6+x/4) + +sin(2/3 - x/4 -/6-x/4) ) *sinx/4 = 1/2 * (sin5/6 + sin(/2 -x/2)) *sinx/4 = 1/2 * (1/2 + cosx/2) *sinx/4 =(1/4)*sinx/4 +1/2*sinx/4*cosx/2 = (1/4)*sinx/4 +(1/4)*( sin(x/4 -x/2) +cos(x/4 +x/2) ) = (1/4)*sinx/4 +(1/4)* sin( -x/4) +(1/4)*cos3x/4 =(1/4)*sinx/4 -(1/4)* sinx/4 + +(1/4)*cos3x/4= (1/4)*cos3x/4. * * * * * * * * * * * * * * * * * * * * * * * * * * использованы формулы : sin(/2 -) =cos и sin*cos =(sin(+) + sin(-))/2 .